Microbial Diversity and Composition is Associated with Patient-Reported Toxicity during Chemoradiation Therapy for Cervical Cancer - Mitra, Aparna (Int J Radiat Oncol Biol Phys, 2020)
BACKGROUND: Patients receiving pelvic radiation for cervical cancer experience high rates of acute gastrointestinal toxicity. The association of changes in the gut microbiome with bowel toxicity from radiation is not well characterized. METHODS: Thirty-five patients undergoing definitive chemoradiation (CRT) underwent longitudinal sampling (baseline, week 1, 3 and 5) of the gut microbiome and prospective assessment of patient-reported gastrointestinal (GI) toxicity. DNA was isolated from stool obtained at rectal exam and analyzed with 16S rRNA sequencing. GI toxicity was assessed with the EPIC instrument to evaluate frequency, urgency, and discomfort associated with bowel function. Shannon diversity index was used to characterize alpha (within sample) diversity. Weighted UniFrac principle coordinates analysis (PCOa) was used to compare beta (between sample) diversity between samples using the PERMANOVA test. LefSe analysis highlighted microbial features which best distinguish categorized patient samples. RESULTS: Gut microbiome diversity continuously decreased over the course of CRT, with the largest decrease at week 5. EPIC bowel function scores also declined over the course of treatment, reflecting increased symptom burden. At all individual time points, higher diversity of the gut microbiome was linearly correlated with better patient reported GI function, but baseline diversity was not predictive of eventual outcome. High toxicity patients demonstrated different compositional changes during CRT, in addition to compositional differences in Clostridia species. CONCLUSIONS: Over time, increased radiation toxicity is associated with decreased gut microbiome diversity. Baseline diversity is not predictive of end-of-treatment bowel toxicity but composition may identify patients at risk for developing high toxicity.